Pecularities of the clinical course of chronic obstructive pulmonary disease in hypertensive patients. - O. L. Arkhipkina (Medičnì Perspektivi)
Nowadays, the problem of comorbid chronic obstructive pulmonary disease (COPD) and arterial hypertension (AH) is considered from the point of view of the presence of common risk factors and pathogenetic mechanisms. The aim of the study was to investigate cardiorespiratory system function in patients with COPD and AH and to analyze the main cardiovascular risk factors. 284 patients with COPD were divided into 2 groups: the main group - 167 patients with COPD and concomitant hypertension, the comparison group - 117 patients with COPD and normal blood pressure values. An analysis of the clinical picture of COPD revealed that patients with AH more often had exacerbation of underlying disease, more expressed clinical manifestations of the disease, differed in phenotypic distribution of patients. All patients with COPD showed a tendency to increase in arterial pressure, blood glucose level and total cholesterol compared with the control group with enhanced tendency in hypertensive patients. In addition, in hypertensive group the patients had a higher body mass index and smoked intensively. According to EGC data, the majority of patients with COPD experienced tachycardia, arrhythmia and conduction disturbances, hypertrophy of ventricules, which occurred more often in hypertensive patients. Pulmonary function was characterized both by obstructive and restrictive changes that were more expressed in the comorbidity. Thus, in the presence of AH the clinical manifestations of COPD varied, demonstrating the contribution of vascular pathology to the respiratory disorders in those patients. The combined course of COPD with AH is characterized by a modification of clinical manifestations of the disease and COPD was associated with increased cardiovascular risk in patients examined.